The Effect of Ownership Structure, Profitability, Firm Size and Tangibility on Capital Structure - Iswarini, Tika; Ardiansari, Anindya (Universitas Negeri Semarang, 2018)
The important decision faced by financial management which relates to the continuity of company operations is funding decision which is capital structure. Capital structure achieves optimal value if the composition of debt and capital are able to increase company value. The purpose of this research is to examine the effect of ownership structure, profitability, firm size, and tangibility against capital structure (research on manufacturing companies listed on Indonesia Stock Exchange period 2012-2016). The population in this research were all manufacturing companies listed on the Indonesia Stock Exchange 2012-2016. This research used purposive sampling method with certain criteria to determine the sample. The sample used was 38 companies with the research period 2012-2016 at manufacturing companies listed on the Indonesia Stock Exchange. Multiple regression analysis using Eviews 8 was used to analyze the data. The result of multiple linear regression test showed that there were three independent variables that affect capital structure they were managerial ownership, firm size and tangibility. Whereas institutional ownership and profitability did not affect the capital structure of manufacturing companies in 2012-2016. The conclusion of this research is managerial ownership, firm size and tangibility have positive and significant effect on capital structure, while institutional ownership and profitability have negative and insignificant effect on capital structure.